HUBUNGAN PENGETAHUAN DAN SIKAP SISWA TENTANG PERILAKU HIDUP BERSIH DAN SEHAT DENGAN TINDAKAN PHBS DI SD SWASTA LUTHER KECAMATAN SIATAS BARITA TAPANULI UTARA TAHUN 2013 - Nelson Tanjung (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2016)
Clean and Healthy behaviors (PHBS) is an attempt to provide a learning experience or creating a condition for individuals, families, groups and communities, with open lines of communication, provide information and to educate to improve knowledge, attitudes and behavior through leadership approaches (advocacy), atmosphere (social support) and empowerment (empowerment) as an attempt to help people recognize and know their own problems, in order of the household, in order to implement ways of healthy living in order to establish, maintain and improve health. Formulation of the problem in this research is how the relationship between knowledge and attitudes of good hygiene practices and healthy with Clean and Healthy behaviors in SD Private Actions Sub Siatas Luther North Tapanuli Banta in 2013. Order to determine the relationship of knowledge and attitudes of good hygiene practices and healthy with PHBs in SD Private Actions Sub Siatas Luther North Tapanuli Banta in 2013. Type of study design is an analytical study using cross-sectional design, in which measurements and observations on the subject of the research carried out all observations. The population in this study were all students in private elementary Luther Class V and Class VI as many as 51 people. Sample is partially or represent the population to be studied. The sample in this study was the entire population (total population) were 51 people. Based on existing research relationships students' knowledge of good hygiene practices and healthy with PHBs action where p value of 0.000. There are students' attitudes about the relationship clean and healthy behaviors with action PHBs where p value of 0.000. Expected to parents and teachers in schools in order to educate and teach children about healthy hygiene practices. To force also in order to make a visit at the school and provide education on healthy hygiene practices on student in primary school.